Labor market discrimination and capital investment: the effects of fan discrimination on stadium investment - Örn B. Bodvarsson; Brad R. Humphreys (Institute for the Study of Labor (IZA), 2009)
We investigate the possibility that labor market discrimination affects economic outcomes in the complementary capital market. Previous research contains ample theoretical justification, and empirical evidence, that discrimination affects wages and employment in labor markets. However, the effects of discrimination against minority labor on transactions in markets for other inputs used in production are not known. We develop a model of the optimal capital stock put in place in the presence of customer discrimination and test this model using data on sports facility construction over the period 1950-2004. The empirical evidence suggests that teams in cities with more racial segregation spend less on sports facilities, confirming the predictions of the model about the effect of customer discrimination on capital investment.
Keywords: J15; 330; Racial discrimination; capital stock; complementarity; stadium financing; Ethnische Diskriminierung; Konsumentenverhalten; Arbeitsmarktdiskriminierung; Einkommen; Kommunale Einnahmen; Sportanlage; Öffentliche Investition; Finanzierung; USA